Ризики у сфері страхування та їх оцінка - Аллахверанов, Р. Ю.; Рожнова, Т. Г.; Солодовник, Г. В. (ХНУРЭ, 2014)
Entrepreneurial activity in any sphere connected with risks due to incomplete information. Questions of qualitative analysis and quantitative risk assessment in the banking sector are the most relevant in connection with the dynamics of this sector, and the high vulnerability to the impacts of the external environment
Keywords: страхування; оцінка ризиків